Observation of an α-synuclein liquid droplet state and its maturation into Lewy body-like assemblies. (2nd January 2021) - Hardenberg, Maarten C; Sinnige, Tessa; Casford, Sam; Dada, Samuel T; Poudel, Chetan; Robinson, Elizabeth A; Fuxreiter, Monika; Kaminksi, Clemens F; Kaminski Schierle, Gabriele S; Nollen, Ellen A A; Dobson, Christopher M; Vendruscolo, Michele
Abstract: Misfolded α-synuclein is a major component of Lewy bodies, which are a hallmark of Parkinson's disease (PD). A large body of evidence shows that α-synuclein can aggregate into amyloid fibrils, but the relationship between α-synuclein self-assembly and Lewy body formation remains unclear. Here, we show, both in vitro and in a Caenorhabditis elegans model of PD, that α-synuclein undergoes liquid‒liquid phase separation by forming a liquid droplet state, which converts into an amyloid-rich hydrogel with Lewy-body-like properties. This maturation process towards the amyloid state is delayed in the presence of model synaptic vesicles in vitro . Taken together, these results suggest that the formation of Lewy bodies may be linked to the arrested maturation of α-synuclein condensates in the presence of lipids and other cellular components.